Strategi Peningkatan Daya Saing Usaha Mikro Kecil Dan Menengah Melalui Peran Serta Pendampingan Indonesia Islamic Bussines Forum Di Palembang - Salim, Abd. Rahman; Sakir, Icuk Muhammad; Iriani, Atrika (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving Indonesia’s economic growth due to their wide distribution across the country. Enhancing the welfare of MSMEs will have a significant impact on the national economy. This study investigates strategies to improve the competitiveness of food-based MSMEs in Palembang using Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and the Analytical Hierarchy Process (AHP). The sample of food MSMEs was selected through purposive sampling. The results of the SWOT and AHP analyses indicate that the priority strategies for strengthening the competitiveness of food MSMEs in Palembang include adopting modern production equipment to enable more efficient and effective product diversification, as well as applying modern management practices to expand market reach both domestically and internationally. In addition, the involvement of mentors or business communities plays an important role in supporting business development. Therefore, collaboration and strong partnerships between the government and MSMEs are essential to enhance their competitiveness and ensure their contribution to economic growth.